ISLAM BAJO: CONSTRUCTION AND CONTESTATION OF RELIGIOUS IDENTITY OF THE BAJO PEOPLE IN WAKATOBI ISLANDS, SOUTH EAST SULAWESI - , Benny Baskara ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Bajo people are known as the sea people. In the past, the Bajo were known as sea gypsies or sea nomads, because they live nomadic on their traditional boats. However, in recent times, most of them are already settled. They build their settlements in shores or atolls, but still on the water, and not on the land. As the sea people, the Bajo have their indigenous belief that is strongly shaped by their natural environment. They believe in Lord of the sea, whom they called Mbo Ma Dilao. The Bajo also acknowledge themselves as Muslim. With this acknowledgement, therefore, the religious identity of the Bajo is a combination between Islamic belief and their indigenous belief. This research focuses on the process of construction and contestation of the Bajo religious identity, especially on two main problems: how do the Bajo construct their religious identity in relation to their natural and social environment and how external influences and challenges to their religious identity are experienced and responded. The method applied for this research is ethnographic method. The observation for this research focuses on the Bajo who live in Wakatobi Islands, Southeast Sulawesi, Indonesia. In the process of construction their religious identity, natural environment is very crucial in the construction of their indigenous belief. Meanwhile, the Bajo were already embraced Islam at the time Islam came to Nusantara archipelago. The contestation to the religious identity of the Bajo are challenges to their religiosity, which can be categorized into three forms: first, challenges from Islam coming from the land to Islamic belief of the Bajo